Hello English Application to Improve the Students' Speaking Skills - Sholihatul Hamidah Daulay; Deasy Yunita Siregar; Noni Sulistia (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
The context of this study is that students' ability to speak English is quite concerning. Students' interest in speaking English is relatively low due to a lack of mastery of vocabulary, and a fear of making mistakes in pronunciation, so they rarely practice it. Students become bored learning English, so their interest in English lessons decreases. Descriptive qualitative research methodologies are used in the research. The research population consisted of MAS PAB 1 Sampali students with a total sample size of 31. The researcher chose 11 students using a purposive sampling technique, in which the sample was determined based on the selection of information sources rather than the number of participants. Methods for gathering data include observation, interviews, and documentation. Data processing involves the reduction of data, the display of data, and the drawing/verification of conclusions. The study's findings are (1) students' perceptions of using the Hello English application revealed that as many as 98% of students believed the application could help improve students' speaking skills, (2) students used Technology progress very well by using it to learn, one of which was using the Hello English application, (3) the Hello English application was very efficient for teachers in helping teach speaking English in class. Based on research findings, the Hello English application is very useful and effective in teaching and learning activities, owing to its easy and practical access on any device, as well as fun features for students that keep them interested in learning English in the future.